Solenostomes and lyrifissures in Paraphytoseius santurcensis De Leon (Acari: Phytoseiidae): comments and voucher photos - Vikram Prasad (Persian Journal of Acarology)
Many photos of solenostomes and lyrifissures, including large gd5, present in female and male Paraphytoseius santurcensis De Leon, 1965, that lacks seta S5, are given. A hypothetical model of Paraphytoseius having seta S5, as in P. cracentis (Corpuz and Rimando, 1966), is included in a line drawing showing all the solenostomes and the lyrifissures that may be present in a species of this genus.